Censorship: Roblox, Wattpad (Vietnam) - Voidly (2024)
CRITICAL severity censorship detected in Vietnam. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: VN-2024-0001
Keywords: censorship; VN; censorship; critical